2014
DOI: 10.1371/journal.pone.0109027
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Image Based Emphysema and Bronchiolitis in HIV-Infected Individuals on Antiretroviral Therapy

Abstract: BackgroundWith the widespread use of anti-retroviral therapy (ART), individuals infected with human immune deficiency virus (HIV) are increasingly experiencing morbidity and mortality from respiratory disorders. However, the prevalence or the risk factors associated with emphysema and bronchiolitis are largely unknown.MethodsThoracic computed tomography (CT) scans were performed in 1,446 patients infected with HIV who were on ART and who attended a tertiary care metabolic clinic (average age 48 years and 29% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
0
31
2
1
Order By: Relevance
“…A number of studies in both the pre-ART and ART eras have demonstrated a link between HIV status and an increased risk of developing COPD/emphysema. 21,25,27,28,32,46,48,49 While evidence exists that this phenomenon may be related to an interaction between HIV infection and smoking, we did not find a significant correlation between CD4 cell count or HIV viral load and Perc950. Our findings are consistent with Samperiz and colleagues who reported no relation between quantitative assessment of emphysema on CT scan and either HIV viral load or CD4 count.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…A number of studies in both the pre-ART and ART eras have demonstrated a link between HIV status and an increased risk of developing COPD/emphysema. 21,25,27,28,32,46,48,49 While evidence exists that this phenomenon may be related to an interaction between HIV infection and smoking, we did not find a significant correlation between CD4 cell count or HIV viral load and Perc950. Our findings are consistent with Samperiz and colleagues who reported no relation between quantitative assessment of emphysema on CT scan and either HIV viral load or CD4 count.…”
Section: Discussioncontrasting
confidence: 92%
“…52 However, they reported that the Center for Disease Control HIV category C was a risk factor for quantitative emphysema and a modest emphysema prevalence (10.5%) using a low emphysema cutoff (greater than 1% of voxels with a value less than -950HU). Three recent studies of HIV-infected cohorts 46,48,52 observed that greater than 30% of the subjects had some evidence of emphysema by visual CT image assessment, which is somewhat higher than our findings of 25.1% by quantitative analysis. However, all three studies reported some significant relation between either nadir or current CD4 count and emphysema.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…For instance, St. George’s Respiratory Questionnaire (SGRQ) scores, which measure respiratory-related health status[6], can demonstrate significant impairment in HIV-infected subjects with otherwise normal spirometry[4]. Similarly, HIV patients with severe emphysema burdens as visualized on computed tomographic (CT) scanning can also have surprisingly well-preserved spirometry[7]. This stands in contrast to HIV-uninfected subjects in whom emphysema quantitation correlates strongly with forced expiratory volume in 1 second (FEV1) measurements[8].…”
Section: Introductionmentioning
confidence: 99%
“…In large, general population COPD cohorts, the presence of emphysema on CT imaging has been associated with increased dyspnea scores and reduced 6 minute walk distances[9], as well as with worse SGRQ scores[10], suggesting that emphysema may be a clinically meaningful marker of disease severity. In HIV-specific populations, the investigation of emphysema has been limited to cross-sectional, descriptive studies that have reported a range of emphysema prevalence from 26% to 53%[7, 1114]. Longitudinal studies looking at the progression of emphysema over time and the risk factors associated with rapid emphysema progression in HIV have yet to be performed.…”
Section: Introductionmentioning
confidence: 99%